The human microbiome project - Weinstock, George (Henry Stewart Talks, 2011)
The microbial genome, our "second genome", Where did our microbiome come from?, Ecological diseases from our microbiome, How to study the human microbiome, Shotgun metagenomic sequencing, The gut microbiome, Viruses and persistent infection in healthy people, Metabolic pathway distribution, Virome analysis, Necrotizing Enterocolitis